KEBERLANJUTAN SUMBER DAYA AKUATIK PADA KAWASAN EKOWISATA MANGROVE LANTEBUNG MAKASSAR - Asrul Muslim; Wayan Kantum; Nursyahran Nursyahran (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
The sustainability of aquatic resources is strongly influenced by the carrying capacity of the environment. This study aims to analyze the sustainability of aquatic resources in the Lantebung mangrove ecotourism area. The research was conducted from October to November 2023 in the Lantebung Makassar mangrove ecotourism area. The method used in this research is a survey method with the Rapfish technique. The results showed that based on the results of Rapfish analysis of the ecological dimension obtained a value of 72.26 classified as sustainable, the economic dimension of 60.51 is sustainable, the social dimension of 67.63 is sustainable and the institutional dimension recorded 57.26 in the moderate category. From these results it can be concluded that the overall sustainability of aquatic resources in the Lantebung area in a multidimensional manner obtained an average value of 64.52 indicating a sustainable status.